Active Thermoplastic Starch Film with Watermelon Rind Extract for Future Biodegradable Food Packaging - Tatsaporn Todhanakasem; Chayanit Jaiprayat; Thunchanok Sroysuwan; Supakanya Suksermsakul; Rachit Suwapanich; Kamolnate Kitsawad Maleenont; Piyawit Koombhongse; Briana M. Young (Polymers, 2022)
. Wrapping fresh-cut purple cabbage with PVA/ST/WMRE film significantly reduced the microbial load after 3 days of storage, in comparison to commercial packaging (PET) and thermoplastic control film. Consumer testing of the packaging film indicated that user acceptance of the product was favorable. Therefore, we suggest that this newly developed film can be used as a biodegradable food packaging item that will lead to enhanced food safety, food quality, prolonged shelf life, and consumer acceptance for further food applications.
Keywords: Nanocomposite Films for Food Packaging; biodegradable polymer synthesis and properties; Food composition and properties